The association of culture with financial satisfaction - Dale, Anita Kaye (Kansas State University, 2014)
This dissertation explores the association of culture with financial satisfaction. Social identity theory, a successor of symbolic interaction framework (Mead, 1930) serves as the theoretical framework for this study, conceptualizing the impact of culture on identity formation through the values, norms, and beliefs of cultures adopted by individuals. Social identity theory also provides an understanding of the power and influence of reference groups supplied by culture through the context provided for the internal determination of satisfaction. The cultures examined (e.g., geography, socioeconomic status, religiosity), each had associations with life domains which influence satisfaction according to well-being research. The associations of cultures with financial satisfaction is a largely unexplored area of research, perhaps due to the difficulty in defining and measuring culture, as well as the challenges associated with influencing financial satisfaction. Data for this study was obtained from the 2012 General Social Survey, conducted by the National Opinion Research Center. This study found the geographic characteristics of home ownership and living in a single family home were associated with financial satisfaction and individuals living in the same state as they did when age 16 had more points of association with financial satisfaction than those not living in the same state. Further, of the SES measures in the study, income was found to be consistently associated with financial satisfaction. Religiosity, including religiosity by religious text (e.g., Bible, Torah, Quran) and prayer were not found to be associated with financial satisfaction. However, frequency of attendance at religious services had a statistically significant association with financial satisfaction and was found to be a moderator of the financial satisfaction of those living in the Eastern and Western U.S. Regions. Understanding the association of culture with financial satisfaction may provide planners with insights into factors which contribute to a client’s values, beliefs and attitudes about their finances. An awareness of the power of cultural values, beliefs and values to influence satisfaction may make a positive contribution to the quality of conversation between planners and clients as they work toward establishing authentic goals and objectives for the client and develop plans to achieve those goals.
Keywords: Financial satisfaction; Culture; Geography; Socioeconomic status; Religion; Religiosity; Individual & Family Studies (0628)